Building resilient communities in Africa to fight famine and food crises: Ugandan farmers fight famine in South Sudan - Pan-Africa Bean Research Alliance (2017)
Earlier this year, South Sudan fell victim to the first famine declared since 2011. Almost six million people are still at risk of starvation. Over 1 million displaced Sudanese are migrating to neighbouring northern Uganda, where they stay in camps for internally displaced people fleeing conflict. Yet, resources to feed the influx of people fleeing South Sudan are scarce. The World Food Programme has reported overwhelming demand for food aid, which has recently been cut due to funding delays. To avoid increasing unrest and migration, a long term food security solution for the region is urgently needed.